The effects of mobile phone use on motor variability patterns during gait - Sarvestan, Javad; Aghaie Ataabadi, Peyman; Svoboda, Zdeněk; Alaei, Fatemeh; Graham, Ryan B (PLoS One, 2022)
Mobile phone use affects the dynamics of gait by impairing visual control of the surrounding environment and introducing additional cognitive demands. Although it has been shown that using a mobile phone alters whole-body dynamic stability, no clear information exists on its impacts on motor variability during gait. This study aimed at assessing the impacts of various types of mobile phone use on motor variability during gait; quantified using the short- and long-term Lyapunov Exponent (λS and λL) of lower limb joint angles and muscle activation patterns, as well as the centre of mass position. Fourteen females and Fifteen males (27.72 ± 4.61 years, body mass: 70.24 ± 14.13 Kg, height: 173.31 ± 10.97 cm) walked on a treadmill under six conditions: normal walking, normal walking in low-light, walking while looking at the phone, walking while looking at the phone in low-light, walking and talking on the phone, and walking and listening to music. Variability of the hip (p λS = .015, λL = .043) and pelvis (p λS = .039, λL = .017) joint sagittal angles significantly increased when the participants walked and looked at the phone, either in normal or in low-light conditions. No significant difference was observed in the variability of the centre of mass position and muscle activation patterns. When individuals walk and look at the phone screen, the hip and knee joints are constantly trying to adopt a new angle to regulate and maintain gait stability, which might put an additional strain on the neuromuscular system. To this end, it is recommended not to look at the mobile phone screen while walking, particularly in public places with higher risks of falls.
Keywords: Gait; užívání mobilních telefonů; Cell Phone Use; Humans; biomechanika; lidé; Female; mužské pohlaví; Male; kolenní kloub; chůze (způsob); Walking; Exercise Test; chůze; Biomechanical Phenomena; ženské pohlaví; Knee Joint; zátěžový test